Presenting a Comprehensive Model for the Socialization of Human Resources in Government Organizations - Salehi, Mohammad; Ghorban Hosseini, Masoud; Sadeh, Ehsan; Amini Sabegh, Zeinoabedin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary objective of this study was to develop and validate a comprehensive model for the socialization of human resources in government organizations. Methodology: This qualitative research employed exploratory interviews and thematic analysis to identify and categorize the components of the socialization model. A purposive sampling method was utilized to select 17 academic and executive experts from government organizations, ensuring a rich, varied collection of insights. The developed model was further validated through a questionnaire distributed among 11 additional academic experts, assessing the fit of the identified themes using a Likert scale. Findings: The analysis revealed a structured socialization model comprising three main themes: components, factors, and outcomes. Components were subdivided into individual, interpersonal, and organizational aspects. Factors included human resource management, structural, behavioral-communicative, and cultural-normative elements. Outcomes highlighted were improving dependency and commitment of employees, organizational development and progress, public satisfaction, preservation and development of human capital, enhancing the spirit of cooperation and interaction, and cohesion and integration. Conclusion: The study successfully presents a validated socialization model tailored for government organizations, particularly within the Agricultural Jihad sector. It underscores the importance of a holistic approach encompassing individual, interpersonal, and organizational components, alongside key influencing factors, to achieve desired socialization outcomes. This model serves as a strategic tool for government organizations to foster a well-integrated, committed workforce capable of driving organizational success and innovation. Future research could extend this model’s applicability across various sectors and cultural contexts to explore its universal effectiveness and adaptability.